2022
DOI: 10.1103/physreve.105.025204
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent relaxation theory of collective ion dynamics in Yukawa one-component plasmas under intermediate screening regimes

Abstract: The self-consistent relaxation theory is employed to describe the collective ion dynamics in strongly coupled Yukawa classical one-component plasmas. The theory is applied to equilibrium states corresponding to intermediate screening regimes with appropriate values of the structure and coupling parameters. The information about the structure (the radial distribution function and the static structure factor) and the thermodynamics of the system are sufficient to describe collective dynamics over a wide range of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…However, these models contain various fitting parameters. This paper presents a theoretical formalism to calculate S(k, ω) of the COCP, which is based on the self-consistent relaxation theory of collective dynamics in multiparticle systems [29,30,[37][38][39][40].…”
Section: Theoretical Formalismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these models contain various fitting parameters. This paper presents a theoretical formalism to calculate S(k, ω) of the COCP, which is based on the self-consistent relaxation theory of collective dynamics in multiparticle systems [29,30,[37][38][39][40].…”
Section: Theoretical Formalismmentioning
confidence: 99%
“…Existing methods either contain adjustable parameters or give satisfactory results in a limited range of wave number values. In this paper, this gap will be filled by use of the self-consistent relaxation theory of collective particle dynamics, which had previously been successfully applied to describe both Yukawa liquids and liquid metals [29,30]. The main results of this work are as follows.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure to understand transport parameters is more accurate as one starts from an unambiguous quantity, the density fluctuations, and is valid for complicated situations like materials with non-pairwise potentials such as warm dense matter etc 29 . Recent studies of OCPs have also shown the estimation of dynamic structure factor in various screening regimes using an alternate approach known as the method of moments 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of the interparticle interaction in the case of the Yukawa system is determined by two key dimensionless parameters: coupling parameter Γ and screening parameter κ [1,2,23]. The coupling parameter…”
mentioning
confidence: 99%